Antisemitism, Islamophobia, and interreligious hermeneutics - Polyakov, Emma O'Donnell. (Currents of Encounter, 2018)
Antisemitism, Islamophobia, and Interreligious Hermeneutics: Ways of Seeing the Religious Other , edited by Emma O'Donnell Polyakov, examines the hermeneutics of interreligious encounter in contexts of conflict. It investigates the implicit judgments of Judaism and Islam that often arise in response to these conflicts, and explores the implications of these interpretations for relations between Jews, Christians, and Muslims. Addressing antisemitism and Islamophobia through the tools of interreligious hermeneutics, this volume brings together three distinct discourses: the study of ancient and new tropes of antisemitism as they appear in today's world; research into contemporary expressions of fear or suspicion of Islam; and philosophical reflections on the hermeneutics of interreligious encounters.